Disruption of epidermal growth factor receptor signaling and cytoskeletal dynamics by mebendazole and gefitinib synergistically impairs paracrine cytokine signaling in non-small cell lung cancer and triple-negative breast cancer Cell lines - Mohamed El-Tanani; Shakta Mani Satyam; Syed Arman Rabbani; Yahia El-Tanani; Mark Sutherland; Frezah Muhana (PLoS ONE, 2025)
Background Aberrant paracrine cytokine signaling and dysregulated signal transduction are critical drivers of tumor progression and therapeutic resistance in aggressive cancers such as non-small cell lung cancer and triple-negative breast cancer. This study aimed to explore a dual-targeting strategy using mebendazole, a repurposed anti-parasitic agent known to disrupt microtubules, in combination with gefitinib, an epidermal growth factor receptor tyrosine kinase inhibitor. The objective was to assess the combinatorial impact on cell viability and key regulatory pathways involved in inflammation, mitotic control, and nuclear transport. Methods Human lung adenocarcinoma (A549) and triple-negative breast cancer (MDA-MB-231) cell lines were treated with mebendazole, gefitinib, or a combination of both. Cell viability in both the cell lines was investigated using the MTT assay, while transcriptional profiling was conducted exclusively in the A549 NSCLC cell line to assess cytokine and regulatory gene modulation. Quantitative reverse transcription polymerase chain reaction was performed to evaluate changes in the expression of inflammatory cytokines (interleukin-1 beta, interleukin-6, TNF-alpha, IFN-gamma) and regulatory genes (MMP-2, STAT 4, RAN, and RCC1). Results Combined treatment with gefitinib (1 µM) and mebendazole (0.5 µM) elicited a pronounced synergistic cytotoxic response, reducing cell viability to ~8–10% in A549 and ~15% in MDA-MB-231 cells—representing an additional >50% and ~30–40% decrease, respectively, compared to the most effective single-agent treatment- gefitinib 1 µM. Gene expression analysis revealed significant downregulation of pro-inflammatory cytokines and alterations in genes involved in mitotic regulation and nuclear transport. These changes suggest impaired intracellular signaling and reduced tumor-supportive microenvironmental interactions. The dual approach disrupted both cytoskeletal architecture and receptor-mediated signal transduction, pointing to a multifaceted mechanism of action. Conclusions The combination of mebendazole and gefitinib effectively suppresses tumor cell viability and modulates key pathways involved in cancer progression. By targeting cytoskeletal integrity and EGFR signaling, it may disrupt cytokine and tumor–microenvironment interactions, supporting further exploration as a strategy to overcome resistance in lung and breast cancers.